Role of Speckle Tracking Echocardiography in Prediction of Responders to Cardiac Resynchronization Therapy - Mohamed Elsayed Abdelfattah; Reda Biomy Bastawisy; Wael Anwar Haseeb; Hany Mahmoud; Abdel-Shakour (Journal of the Pakistan Medical Association, 2023)
Objective: To assess heart failure patients by speckle tracking echocardiography before cardiac resynchronisation therapy implantation to predict the outcome. Method: The descriptive follow-up study was conducted at Kafrelsheikh and Mansoura University Hospitals, Egypt, from January 2020 to May 2022, and comprised heart failure patients of either gender who had ejection fraction ≤35%, QRS width ≧130msec and symptomatic even on optimal medical therapy. They were subjected to full clinical evaluation, electrocardiogram, basic and speckle tracking echocardiography with calculation of maximal septal to lateral delay at baseline and 3 months after cardiac resynchronisation therapy implantation. The patients were classified according to response into group I having non-responders, group II having patients who improved clinically only, and group III having responders both in clinical and echocardiographic terms. Data was analysed using SPSS 23. Results: Of the 38 patients with mean age 55.24±11.23 years, 16(42%) were females and 22(57.9%) were males. There were 7(18.4%) patients in group I, 7(18.4%) in group II and 24(63.2%) in group III. There was a positive significant correlation between response to cardiac resynchronisation therapy CRT and increase in maximal septal to lateral delay at baseline (p<0.01). There was an inverse significant correlation between response to cardiac resynchronisation therapy and decrease in maximal septal to lateral delay 3 months after the implantation (p=0.036). Conclusion: Maximal septal to lateral delay was found to be a good tool to predict the response to cardiac resynchronisation therapy before implantation. Keywords: Speckle tracking, Cardiac resynchronisation therapy, Heart failure